IMPACT OF SPORTS ACTIVITIES ON THE DECREASE OF STIGMA PLWHA (People With HIV/AIDS) AND SOCIAL VALUES OF RUMAH CEMARA BANDUNG - Megia Erida (Universitas Pendidikan Indonesia, 2019)
Sports activities are activities that can be carried out by all groups with the aim of improving the quality of life in terms of physical fitness and psycho-social well-being. People who suffer from HIV/AIDS often get negative stigma and changes in social values. This study was aimed at determining the decrease in stigma and changes in the social value of PLWHA (people with HIV / AIDS) through futsal Rumah Cemara Bandung sports activities. The method used in this study was a comparative causal method (ex-post facto). Design of the study used criteria group. The technique of sampling in this study used convience sampling technique. The sample of this study consisted of 20 people divided into two groups: 10 PLWHA who were active in sports and 10 PLWHA who were not active in sports. Data collection process was conducted through face-to-face interview and structured questionnaire. Based on validity and reliability tests, researchers used an adopted questionnaire and discussed the questionnaire with the expert. Data analysis was conducted by using SPSS version 23 employing independent sample T-test. The results of this study indicate a decrease in stigma and changes in social values seen from T test with tcount ttable. The conclusions from the Stigma calculation was 3.439 2.10092 and Social Value was 3.730 2.10092. The result concludes that sports activities have an effect on reducing the stigma and changes in the Social Value of PLWHA.